2015
DOI: 10.1080/03602559.2015.1050517
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Prepare Poly(Vinyl Acetate)/Ag Nanocomposite for Effective Antimicrobial Coating Applications

Abstract: Polyvinyl acetate (PVAc) nanocomposites were successfully prepared based on silver nanoparticles (Ag-NPs). Firstly, Ag-NPs was directly prepared during the in situ emulsion polymerization of vinyl acetate monomer using AgNO 3 as a source of Ag + ions and poly(vinyl alcohol) (PVA) was used for dual functions as emulsifier for emulsion polymerization and a s stabilizer agent, tri-sodium citrate (C 6 H 5 O 7 Na 3 ) was used as reducing agent for Ag + ions during the polymerization process. The prepared PVAc/Ag na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recent studies have reported the use of silver, zinc oxide, and titanium oxide NPs in the development of antibacterial nanopackaging films. However, the major drawback of this process is the migration of these nanoparticles from the packaging materials to the food samples, causing carcinogenicity [13,14].…”
Section: Incorporation Of Nanomaterialsmentioning
confidence: 99%
“…Recent studies have reported the use of silver, zinc oxide, and titanium oxide NPs in the development of antibacterial nanopackaging films. However, the major drawback of this process is the migration of these nanoparticles from the packaging materials to the food samples, causing carcinogenicity [13,14].…”
Section: Incorporation Of Nanomaterialsmentioning
confidence: 99%
“…Presence of the plant extract reduced formation of AgNO 3 into Ag ions. Moreover, the secondary metabolites present in the extract act as a reducing and a capping agent for Ag-NPs synthesis [74][75][76][77][78].…”
Section: Assessment Of the Structure And Morphology Of Fabricated Nanmentioning
confidence: 99%